Organizações regionais indígenas, cidadania e tecnologias de (des)informação e (in)comunicação na Pan-Amazônia - PARRA MONSALVE, James León (Universidade Federal do Pará, 2019)
The Amazon is an extensive South American area, shared by eight countries and a French overseas department. It is now widely known for its social and environmental diversity. The existence of indigenous and other traditional peoples over that territory, has historically been crucial for the conservation of common ways to access and use the land. In this context, indigenous movements have developed an important organizational structuring task, especially starting from the 1970s, in order to claim such rights within the nation-state. Thus, they have set up new agencies in the struggle for full recognition of their citizen status in countries like Bolivia, Ecuador, Peru, Colombia, Venezuela and Brazil. As a consequence of organizational articulation and, even more, the historical resistance of indigenous peoples to the physical and symbolic disintegration, the new political constitutions in those countries recognized the ethnic and multicultural character of their societies. Regional ethnic organizations emerged like the Confederation of Indigenous Peoples of the East, Chaco and Amazon of Bolivia (CIDOB), the Coordination of Indigenous Organizations of the Brazilian Amazon (COIAB), the Organization of Indigenous Peoples of the Colombian Amazon (OPIAC), the Confederation of Indigenous Nationalities of the Ecuadorian Amazon (CONFENIAE), the Inter-ethnic Association of the Peruvian Rainforest Development (AIDESEP) and the Regional Organization of Indigenous Peoples of the Amazon (ORPIA) in Venezuela. Organizations that reach the twenty-first century with the responsibility to claim the rights of multiple people representing, with new tools such as Information and Communication Technologies (ICTs), which could, in varying degrees, leverage this social goal. This comparative study allows us to understand the relationship of ethnic-citizen claims with indigenous knowledge about communication and the way they produce information and communication.